Odd is on our side - Van Lente, Fred.; Chan, Queenie; Koontz, Dean R. (Dean Ray), 1945- (London : HarperCollins, 2010)
With Halloween approaching, fry cook Odd Thomas begins to feel like something evil is lurking in Pico Mundo, California, and, with the help of his girlfriend and the ghost of Elvis Presley, he sets out to uncover the truth.
Young Adult.
Young Adult
Keywords: Cooks -- Comic books, strips, etc -- Fiction; Mediums -- Comic books, strips, etc -- Fiction; Thomas, Odd (Fictitious character) -- Comic books, strips, etc; Young men -- Comic books, strips, etc -- Fiction; Comic books, strips, etc; Cooks -- Comic books, strips, etc -- Fiction; Ghost stories; Graphic novels; Horror graphic novels; Mediums -- Comic books, strips, etc -- Fiction; Thomas, Odd (Fictional character) -- Comic books, strips, etc; Young men -- Comic books, strips, etc -- Fiction; Ghost stories; Graphic novels; Horror comic books, strips, etc